Examining the Protein Interactome and Subcellular Localization of RNase J2 Complexes in Streptococcus mutans - Mu, Rong; Shinde, Pushkar; Zou, Zhengzhong; Kreth, Jens; Merritt, Justin (Frontiers in Microbiology, 2019)
Regulated RNA turnover is vital for the control of gene expression in all cellular life. In E. coli, this process is largely controlled by a stable degradosome complex containing RNase E and a variety of additional enzymes. In the Firmicutes phylum, species lack RNase E and often encode the paralogous enzymes RNase J1 and RNase J2. Unlike RNase J1, surprisingly little is known about the regulatory function and protein interactions of RNase J2, despite being a central pleiotropic regulator for the streptococci and other closely related organisms. Using crosslink coimmunoprecipitation in Streptococcus mutans, we have identified the major proteins found within RNase J2 protein complexes located in the cytoplasm and at the cell membrane. In both subcellular fractions, RNase J2 exhibited the most robust interactions with RNase J1, while additional transient and/or weaker ‘degradosome-like’ interactions were also detected. In addition, RNase J2 exhibits multiple novel interactions that have not been previously reported for any RNase J proteins, some of which were highly biased for either the cytoplasmic or membrane fractions. We also determined that the RNase J2 C-terminal domain encodes a structure conserved among RNase J enzymes that has an analogous function to that of RNase E.